Governo de esquerda e gasto público: um estudo a partir de Diadema (1983-2000) - Pinto, Daniela Cardoso (2008)
This dissertation tries to evaluate if the expenditures on social policies introduced at the municipality of Diadema by left-wing parties from 1983 to 2000 differ from the expenditures at other municipalities of the same region of the Great ABC, which administrations were conducted by parties of both leftist and rightist parties. It intends to answer if the right-left ideological cleavage caused different patterns of public expenses, or if despite the ideological cleavages, diverse patterns of public expenditures could be caused by other reasons, such as: different kinds of policy demands at different municipalities the region; differences of style of the public managers; or if simply there were no differences of public expenditures between the municipalities. To frame de database of this research we used information from the account offices of each municipality and also information available at the internet pages of Seade Foundation, National Secretary of Treasure and Brazilian Institute of Geography and Statistics. Besides, we used interviews with some political actors in order to support our analysis